2019
DOI: 10.1111/ejn.14514
|View full text |Cite
|
Sign up to set email alerts
|

The enduring effects of early‐life stress on the microbiota–gut–brain axis are buffered by dietary supplementation with milk fat globule membrane and a prebiotic blend

Abstract: Nutritional interventions targeting the microbiota–gut–brain axis are proposed to modulate stress‐induced dysfunction of physiological processes and brain development. Maternal separation (MS) in rats induces long‐term alterations to behaviour, pain responses, gut microbiome and brain neurochemistry. In this study, the effects of dietary interventions (milk fat globule membrane [MFGM] and a polydextrose/galacto‐oligosaccharide prebiotic blend) were evaluated. Diets were provided from postnatal day 21 to both n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 70 publications
(105 reference statements)
2
33
0
Order By: Relevance
“…While more mechanistic investigations are necessary, it is possible that changes in the abundance of Parabacteroides may play a role in the beneficial impact of dietary interventions on behavior. This is in line with our previous findings related to the effects of a blend of prebiotics (polydextrose/galacto-oligosaccharide prebiotic blend) positively influencing behaviour and brain gene expression while also increasing the abundance of parabacteroides [65].…”
Section: Discussionsupporting
confidence: 93%
“…While more mechanistic investigations are necessary, it is possible that changes in the abundance of Parabacteroides may play a role in the beneficial impact of dietary interventions on behavior. This is in line with our previous findings related to the effects of a blend of prebiotics (polydextrose/galacto-oligosaccharide prebiotic blend) positively influencing behaviour and brain gene expression while also increasing the abundance of parabacteroides [65].…”
Section: Discussionsupporting
confidence: 93%
“…There is a growing interest in developing strategies to manipulate the microbiota as a potential therapeutic intervention in the treatment of cardiorespiratory disease. Rodent and human studies have revealed that prebiotic administration has positive impacts on brain neurochemistry and functions [ 30 , [41] , [42] , [43] , [44] ]. Moreover, prebiotic feeding prevented the development of hypertension in a rat model of OSA [33] .…”
Section: Introductionmentioning
confidence: 99%
“…The potential contributions to the infant immune system by MFGM and its individual components, such as lactadherin and gangliosides, have been reviewed [5]. The most commonly reported immune modulatory effects consist of shifts in balance favoring anti-inflammatory over inflammatory cytokines [134][135][136], providing protection from inflammatory damages within the intestine [114][115][116][117]137], and modulating the gut microbiome [109,[118][119][120][121][122]138,139]. The role of MFGM in modulating the microbiome is still currently an ongoing discussion, as many of the studies cited have multiple nutritional interventions (other prebiotics or different fat sources).…”
mentioning
confidence: 99%